L’évaluation des programmes d’études réorientée par l’utilisation d’un modèle de simulation - Piedalue, Gilles; Feuvrier, Pierre (Canadian Journal of Higher Education, 1984)
This article proposes first a synthetical and operational definition capable of integrating the political and technical aspects of institutional evaluation of academic programs. Second, it presents a model that takes into account the complex problem of evaluation. When the model is used on a computer, it makes the process of his reduction to the requirements of the institutional environment more dynamic.